2021
DOI: 10.1161/jaha.120.020521
|View full text |Cite
|
Sign up to set email alerts
|

Serine 26 in Early Growth Response‐1 Is Critical for Endothelial Proliferation, Migration, and Network Formation

Abstract: Background Vascular endothelial cell proliferation, migration, and network formation are key proangiogenic processes involving the prototypic immediate early gene product, Egr‐1 (early growth response‐1). Egr‐1 undergoes phosphorylation at a conserved Ser26 but its function is completely unknown in endothelial cells or any other cell type. Methods and Results A CRISPR/Cas9 strategy was used to introduce a homozygous Ser26>Ala mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…The reduction of EGR1 in Pdgfra GFP/GFP XY KI gonads suggest that EGR1 might be involved in vascular development of XY gonads. EGR1-knockout human vascular endothelial cells exhibit slower rates of proliferation and migration 45 , and here our analyses revealed that Egr1-knockdown mouse gonadal and mesonephric cells showed significantly compromised cell migration. Taken together, disruptions in vascular development in Pdgfra GFP/GFP XY KI gonads might be due to a deficiency in Egr1-mediated cell migration.…”
Section: Discussionsupporting
confidence: 60%
“…The reduction of EGR1 in Pdgfra GFP/GFP XY KI gonads suggest that EGR1 might be involved in vascular development of XY gonads. EGR1-knockout human vascular endothelial cells exhibit slower rates of proliferation and migration 45 , and here our analyses revealed that Egr1-knockdown mouse gonadal and mesonephric cells showed significantly compromised cell migration. Taken together, disruptions in vascular development in Pdgfra GFP/GFP XY KI gonads might be due to a deficiency in Egr1-mediated cell migration.…”
Section: Discussionsupporting
confidence: 60%
“…Santiago et al found that ERK1 (Mitogen-Activated Protein Kinase 3) could phosphorylate the serine residue at the 26th position (Ser26) in EGR1 in human vascular endothelial cells, which has a protective effect against apoptosis. If Ser26 is mutated, endothelial cells will undergo apoptosis ( 24 ). In one study, Fasolo et al determined the effect of the long non-coding RNA myocardial invasion-associated transcript (MIAT) on advanced atherosclerotic lesions.…”
Section: Egr-1 Is Involved In Cardiac Cell Deathmentioning
confidence: 99%
“…Early growth response-1 (EGR-1) is an important upstream transcription factor that regulates cell proliferation and differentiation and plays an essential role in tumor angiogenesis ( 28 , 29 ). EGR-1 is a common intermediate of VEGF and fibroblast growth factor (FGF) in regulating cell function ( 30 ).…”
Section: Normalization Of Tumor Vasculaturementioning
confidence: 99%